Does cleft palate repair reduce the incidence of middle ear pathology? - Sunil Kumar Rout; Sudarsan Baliarsing; Manoj Kumar Lath; Aparajita Debnath; Suresh Prasad Dash (Journal of Cleft Lip Palate and Craniofacial Anomalies, 2016)
Introduction: In an infant, cleft palate usually affects his/her feeding, speech, eustachian tube, and middle ear physiology. The incidence of otitis media with effusion is particularly very high in the children having cleft palate. Repair of cleft palate is believed to reduce this incidence. Objective: This study was conducted to assess the effect of cleft palate repair on middle ear physiology. Methodology: The study sample was divided into two groups: Group A consists of patients who are 6 years and older with unrepaired cleft palate and Group B of the patients whose cleft palate were repaired before the age of 2 years and completed at least 4 years after surgery. There were thirty patients in each group. All of them were evaluated clinically, by otoscopy and tympanometry. Clinical assessment included examination of the palate in terms of the presence of scarring, fistula, length of soft palate (visual assessment only), mobility of the soft palate, and speech scoring by Pittsburgh weighted speech score. Results: About 21% of operated patients had velopharyngeal incompetence. Thirty-four ears (56.6%) in Group A and 24 ears (40.6%) in Group B had normal otoscopy finding. Normal tympanogram (Type A curve) was found in exactly similar proportion of ears examined in both the groups (20% each). Conclusion: Early repair of cleft palate did not have any beneficial effect on middle ear pathology.